Acute Isolated Thenar Compartment Syndrome in a Patient with Evans Syndrome: A Case Report - Elisabeth Jiang; Kevin H. Kim; Alan Babigian (Clinical Practice and Cases in Emergency Medicine, 2022)
Introduction: Acute compartment syndrome of the hand is a rare medical emergency, most often associated with trauma or fracture. Case Report: Here, we describe a rare case of isolated thenar compartment syndrome of the hand in the absence of major trauma as the presenting symptom of pancytopenia due to Evans syndrome, an uncommon autoimmune hematologic disorder. Conclusion: In cases of atraumatic compartment syndrome, it is critical to evaluate for underlying coagulopathy in patients presenting to the emergency department.